CINTA DAN RUPIAH TERHADAP KUALITAS PENDIDIKAN ISLAM DAN SOSIAL MASYARAKAT BUGIS DI DESA DALIL KEC BAKAM DAN SUNGAI LIAT - DG Tujuhsyarifah21 HR (Tarbawy : Jurnal Pendidikan Islam, 2023)
Love is one of the basic things that exists to perfect a couple’s marriage as they navigate the household. In Bugis society apart from love, rupiah is also an important thing that must exist before stepping into marriage. Usually this rupiah is termed Panaik Money. For the Bugis community, there is no banknote/rupiah, so there is no marriage. Even when two lovebirds like each other and even fail to get married because there is no agreement regarding the rupiah that the man must hand over to the woman in a fantastic amount, then something called silariang or elopement appears. In this study, researchers will see how the position of the rupiah is if it has been linked to Islamic education and social education. Giving Panaik money in traditional Bugis Makassar marriages is not regulated in Islamic law. Islamic law only requires the prospective groom to pay a dowry to the prospective bride and even then it is recommended for the woman not to ask for excessive dowry.The amount of Panaik money that must be submitted depends on the social status, education, physical condition, and occupation of the prospective bride. The higher the social status of his future wife, the higher the amount that must be given. Social education is related to the values contained in giving rupiah, which are sometimes fantastic amounts, especially the transmigrant community in the Bangka Belitung Islands. In this study, the Bugis community in Kec. Bakam and Clay River. Research data was collected using interview techniques and documentary observation.